Who feels it? Income inequality, relative deprivation, and financial satisfaction in U.S. states, 1973-2012. (April 2019) - Hastings, Orestes P.
Highlights: As income inequality rises, individuals may be less financially satisfied as they feel increasingly deprived relative to others. I analyze 1973–2012 General Social Surveys linked to state-level administrative data. Higher income inequality decreases financial satisfaction overall. The negative effect is especially pronounced for those in the middle of the income distribution. Counterfactual simulations suggest rising inequality explains a substantial portion of a four-decade decline in financial satisfaction. Abstract: Many accounts posit that as income inequality rises, individuals will be less satisfied with their own financial situation as they feel increasingly deprived relative to others—driving these individuals to spend more as they engage in positional competition and increasing their anxieties as position in the income distribution becomes ever more important. I examine if and for whom income inequality reduces financial satisfaction by analyzing the 1973–2012 General Social Surveys linked to state-level administrative data based on tax returns, the Census, and the American Community Survey. I find that higher state-level income inequality decreases financial satisfaction overall, and I further find that this effect is especially pronounced for those in the middle of the income distribution. Counterfactual simulations suggest rising income inequality explains a substantial portion of a four-decade decline in financial satisfaction.